2009
DOI: 10.1073/pnas.0904849106
|View full text |Cite
|
Sign up to set email alerts
|

Pdx1 ( MODY4 ) regulates pancreatic beta cell susceptibility to ER stress

Abstract: Type 2 diabetes mellitus (T2DM) results from pancreatic ␤ cell failure in the setting of insulin resistance. Heterozygous mutations in the gene encoding the ␤ cell transcription factor pancreatic duodenal homeobox 1 (Pdx1) are associated with both T2DM and maturity onset diabetes of the young (MODY4), and low levels of Pdx1 accompany ␤ cell dysfunction in experimental models of glucotoxicity and diabetes. Here, we find that Pdx1 is required for compensatory ␤ cell mass expansion in response to diet-induced ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
174
1
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 207 publications
(192 citation statements)
references
References 33 publications
(34 reference statements)
11
174
1
3
Order By: Relevance
“…Meis family members form heterodimeric and -trimeric complexes with Pbx and/or Pdx1 to regulate gene expression in acinar and ductal cells; however, the potential Meis binding site in the Pdpk1 promoter does not contain nearby consensus-binding sequences for Pbx or Pdx1. Further, Pdpk1 was not dysregulated in cDNA expression arrays examining Pdx1-deficient Min6 and primary islets cells (20). It will be interesting to determine whether Meis3 functions in concert with Pdx1 and/or Pbx family members or as an independent monomeric factor in regulating Pdpk1 gene expression.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Meis family members form heterodimeric and -trimeric complexes with Pbx and/or Pdx1 to regulate gene expression in acinar and ductal cells; however, the potential Meis binding site in the Pdpk1 promoter does not contain nearby consensus-binding sequences for Pbx or Pdx1. Further, Pdpk1 was not dysregulated in cDNA expression arrays examining Pdx1-deficient Min6 and primary islets cells (20). It will be interesting to determine whether Meis3 functions in concert with Pdx1 and/or Pbx family members or as an independent monomeric factor in regulating Pdpk1 gene expression.…”
Section: Discussionmentioning
confidence: 98%
“…Islet isolations from 10-wk-old wild-type C57/Bl6 males were performed using collagenase digestion similarly to previously described protocols (20). After anesthetizing each mouse, the pancreas was inflated with cold 1× Hank's buffer containing 0.2% collagenase (Crescent Chemical).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent findings have established that opening of the MPTP is a component of the ER stress response, including in β-cells (32,33). Sachdeva et al recently reported that Pdx1 deficiency enhances β-cell susceptibility to ER stress-associated apoptosis (34). Thus, accumulated data indicate that the mitochondrial permeability transition plays a significant role in programmed cell death via metabolic shutdown and the ER stress response.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that Atf6 and Xbp1 are "housekeeping" rather than stress response genes in the ␤-cell (53), and our data are consistent with this hypothesis. It was recently reported that islets of Pdx1 (MODY4) haploinsufficient mice are sensitized to ER stress through reduction of Atf4 and its target genes (54), showing that another MODY gene can play an important role in maintenance of ER function as well as ␤-cell development. However, we observed a positive rather than negative effect of DN-Hnf1␣ on Atf4 (Fig.…”
Section: Discussionmentioning
confidence: 99%